Analisis Kesulitan Siswa pada Materi Pecahan - Unaenah, Een; Rohmah, Nafisah Nur; Sefani, Nur Aliza (MASALIQ, 2023)
The study aims to see if children in elementary school are able to grasp the concept of a simple fraction by which tests are given about whether the child is struggling with his performance. In this study using qualitative descriptive research. The methods used include interviews, tests, and analyzing. With the introduction of a test can be seen the child's academic ability to complete different tests where it is viewed as difficulties in the work being an indication of student misunderstanding of the concept of fraction.